Dangerous alliance - Cohen, Jennieke (2019)
Lady Victoria Aston, obsessed with Jane Austen and content to stay home, is suddenly expected to enter society and find a husband, preferably one who cares for her more than her dowry.
"An Austentacious romance"--Jacket.
Keywords: Aristocracy (Social class) -- Fiction; Marriage -- Fiction; Mate selection -- Fiction; Aristocracy (Social class) -- Juvenile fiction; Marriage -- Juvenile fiction; Great Britain -- History -- George III, 1760-1820 -- Fiction; Great Britain -- History -- George III, 1760-1820 -- Juvenile fiction; Young adult fiction; Historical fiction; Romance fiction